2013
DOI: 10.1002/pd.4212
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of placental T21 mosaicism: challenging the detection limits of non‐invasive prenatal testing

Abstract: What's already known about this topic? Confined placental mosaicism (CPM) is a known biological phenomenon that can lead to false positive non-invasive prenatal test results. The small number of false negative non‐invasive prenatal test results reported to date are believed to be because of a low fetal DNA fraction in maternal plasma and/or placental mosaicism What does this study add? The degree and compartmentalization of placental mosaicism can potentially reduce the effective output of fetal DNA into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 10 publications
3
48
1
1
Order By: Relevance
“…(1) maternal CNVs, maternal mosaicism, 21 maternal cancers or haematological malignancies, 22 and confined placental mosaicism (CPM) [23][24][25][26][27][28][29][30][31][32][33][34] may cause variability of the sequence read count statistics, which could mask or mimic true aneuploidy-related variation, and may, in turn, result in false-positive or false-negative results; (2) the degradation and/or apoptosis of maternal cells following maternal blood sampling would increase the maternal fraction in the plasma and as a consequence reduce the fetal fraction. A low fetal fraction could cause false-negative results and maternal cell degradation may result in low-quality experiments, which can cause false-positive or false-negative results.…”
Section: Introductionmentioning
confidence: 99%
“…(1) maternal CNVs, maternal mosaicism, 21 maternal cancers or haematological malignancies, 22 and confined placental mosaicism (CPM) [23][24][25][26][27][28][29][30][31][32][33][34] may cause variability of the sequence read count statistics, which could mask or mimic true aneuploidy-related variation, and may, in turn, result in false-positive or false-negative results; (2) the degradation and/or apoptosis of maternal cells following maternal blood sampling would increase the maternal fraction in the plasma and as a consequence reduce the fetal fraction. A low fetal fraction could cause false-negative results and maternal cell degradation may result in low-quality experiments, which can cause false-positive or false-negative results.…”
Section: Introductionmentioning
confidence: 99%
“…In the case presented here, the proportion of the 8.5% fetal fraction that derived from trisomy 13 positive extraembryonic tissues was likely less than half, thus decreasing the functional fetal fraction to less than the level required. Similar patterns of mosaicism have been reported in cases with false negative cfDNA screening results [3,13,18]. This type of fetoplacental mosaicism is different from CMP, which is more commonly reported etiology for discordant cfDNA and fetal/infant cytogenetic results.…”
Section: Discussionmentioning
confidence: 56%
“…For trisomies 18 and 21, this mechanism has been recently described. A false negative trisomy 18 cfDNA screening result due to 48, XXX, +18 placental mosaicism and two cases with false negative trisomy 21 due to placental mosaicism have been reported [3,13]. Potential contribution of fetoplacental mosaicism to discordant cfDNA screening results has been reported; this study suggested that the sensitivity or specificity of cfDNA screening will never reach 100% due to the nature of fetoplacental mosaicism.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations